The Effect Of Project-Based Learning On Students’ Recount Text Writing At SMP Negeri 1 Pematangsiantar - Vercelly Hot Taruli Manik; Selviana Napitupulu (Jurnal Ilmu Pendidikan dan Sosial, 2026)
Writing is a crucial yet challenging skill for English as a Foreign Language (EFL) learners. Many Indonesian students experience difficulties in organizing ideas, applying correct tenses, and producing coherent paragraphs, particularly in writing recount texts. This study aimed to examine the effect of Project-Based Learning (PBL) on ninth-grade students’ ability to write recount texts at SMP Negeri 1 Pematangsiantar. The research used a pre-experimental design with a one-group pretest–posttest model involving 31 students. A writing test was administered as the instrument, assessing five aspects: content, organization, grammar, vocabulary, and mechanics. Quantitative data were analyzed using descriptive statistics by comparing mean scores from the pre-test and post-test. The findings revealed a significant improvement in students’ writing performance, with the mean score increasing from 63.0 to 79.0, representing a 16-point (25.4%) gain. Notable improvement occurred in content and organization, indicating clearer idea development and better text structure. The study concludes that Project-Based Learning effectively enhances students’ engagement, creativity, and writing competence in EFL classrooms.